4 - Managing Multiple Modalities of Delivering Basic Services in Ghanaian Cities: 10.4314/ad.v27i2.22165 - Awortwi, Nicholas (Africa Development, 2022)
This paper analyses the capacity of three local governments (LGs) in Ghana to undertake new ways of solving public problems in basic infrastructure services. The paper argues that while LGs in Ghana have disengaged themselves in di rectly delivering public sanitation and solid waste (SSW) services to users and have pursued multiple modalities of public, private and community delivery, they have found themselves trying to manage complicated new relationships for which their competence is insufficient. The paper further argues that adoption of new and different modalities does not guarantee automatic realization of LG goals. The paper concludes that contracting out government services to multi ple agents is a difficult process whose expectation can easily be elusive, so there should be systematic analysis of LG regulatory, facilitative and monitoring ca pacities before undertaking that new approach. The paper suggests that becom ing a purchaser rather than a provider entails a new administrative capacity of government workers supported by a new information and management process. Managing multiple modalities to achieve expected outcomes is different from managing traditional bureaucracy.